AI-Enabled Human Capital For Organizational Resilience and Competitiveness - Rida Justin Jacobalis; Iman Sjamsu Rahardjo; Sri Rahayu; Albiansyah Albiansyah; Desika Andriani (Jurnal Minfo Polgan, 2026)
The rapid advancement of Artificial Intelligence (AI) has transformed how organizations build and sustain competitive advantage. However, investments in AI alone are insufficient to achieve sustainable competitiveness without the support of strong organizational capabilities. This study aims to develop a conceptual framework that explains the strategic role of AI-enabled Human Capital in enhancing Organizational Resilience and Sustainable Competitiveness. Using a Conceptual Literature Review (CLR) approach, the study synthesizes complementary theoretical perspectives, including Human Capital Theory, the Resource-Based View, Dynamic Capabilities Theory, and Risk Governance Theory, supported by contemporary literature on artificial intelligence, strategic management, financial policy, risk governance, and organizational resilience. The study proposes an Integrated Strategic Capability Framework that explains how organizations transform AI investments into sustainable competitive advantage through the interaction of four strategic capabilities: Financial Policy, Risk Governance, AI-enabled Human Capital, and Organizational Resilience. Within this framework, AI-enabled Human Capital is positioned as the central strategic capability that integrates human expertise, AI technologies, organizational learning, and strategic decision-making. The proposed framework contributes to the theoretical development of AI-driven strategic management while offering practical guidance for organizations in designing AI-based transformation strategies. Nevertheless, further empirical studies are required to validate the proposed framework across diverse organizational contexts.